Exploring the Impact of Combined Thai Yoga and Elastic Band Exercise on Physical Fitness and Exercise Capacity in Older Patients with Type 2 Diabetes - Muangritdech, Nattha; Promsrisuk, Tichanon; Kongsui, Ratchaniporn; Sriraksa, Napatr; Thongrong, Sitthisak; Srithawong, Arunrat (Physical Education Theory and Methodology, 2023)
Study purpose. Although it is acknowledged that exercise can positively affect both physical and biochemical markers in older individuals with type 2 diabetes (T2DM), there are still uncertainties about the specific impacts of combining Thai yoga with an elastic band exercise in this population. The objective of the study was to assess the impact of a 12-week program involving Thai yoga combined with an elastic band exercise on the physical fitness and functional exercise capacity among older individuals with T2DM. Materials and methods. A total of 42 participants, consisting of 20 men and 22 women with T2DM and a mean age of 64.6±3.6 years, were randomly assigned to two groups: the control group and the exercise group. The exercise group engaged in a daily regimen of Thai yoga combined with an elastic band exercise for 40 minutes, 5 days a week, over a 12-week period. In contrast, the control group maintained their regular routines. Physical fitness and functional exercise capacity were assessed both before and after the 12-week intervention. Results. The exercise group showed significant reductions in body weight (58.7±11.9 vs. 58.0±12.0 kg), body mass index (24.2±3.0 vs. 23.9±3.0 kg/m2), waist circumference (33.6±3.6 vs. 33.1±3.6 in), and waist-hip ratio (0.90±0.06 vs. 0.89±0.06) (p < 0.001). Additionally, there were notable improvements in physical fitness parameters, including hand grips, back strength, leg strength (p < 0.01), and trunk flexibility (p < 0.001). Functional exercise capacity, indicated by the 6-minute walk test and estimated peak oxygen consumption (p < 0.01), also improved significantly. Conclusions. Thai yoga combined with an elastic band exercise enhances physical fitness and functional exercise capacity in older individuals with T2DM. This improvement has the potential to enhance their cardiopulmonary performance. Consequently, this exercise regimen is considered a health alternative for older individuals with T2DM.